Decreasing the Surgical Errors by Neurostimulation of Primary Motor Cortex and the Associated Brain Activation via Neuroimaging - Gao, Yuanyuan; Cavuoto, Lora; Dutta, Anirban; Kruger, Uwe; Yan, Pingkun; Nemani, Arun; Norfleet, Jack E.; Makled, Basiel A.; Silvestri, Jessica; Schwaitzberg, Steven; Intes, Xavier; De, Suvranu (Frontiers in Neuroscience, 2021)
Acquisition of fine motor skills is a time-consuming process as it is based on learning via frequent repetitions. Transcranial electrical stimulation is a promising means of enhancing simple motor skill development via neuromodulatory mechanisms. Here, we report that non-invasive neurostimulation facilitates the learning of complex fine bimanual motor skills associated with a surgical task. During the training of 12 medical students on the Fundamentals of Laparoscopic Surgery (FLS) pattern cutting task over a period of 12 days, we observed that transcranial direct current stimulation (tDCS) decreased error level and the variability in performance, compared to the Sham group. Furthermore, by concurrently monitoring the cortical activations of the subjects via functional near-infrared spectroscopy (fNIRS), our study showed that the cortical activation patterns were significantly different between the tDCS and Sham group, with the activation of primary motor cortex (M1) and prefrontal cortex (PFC) contralateral to the anodal electrode significantly decreased while supplemental motor area (SMA) increased by tDCS. The lowered performance errors were retained after one-month post-training. This work supports the use of tDCS to enhance performance accuracy in fine bimanual motor tasks.